Robustness evaluation of fuzzy-based NCTF control of Point-To-Point(PTP) positioning systems - Martono, Wahyudi; Ibrahim, Tarig. F.; Salami, Momoh Jimoh Eyiomika (2007)
The positioning systems generally need a good controller to achieve high accuracy, fast response and robustness. In addition, ease of controller design and simplicity of controller structure are very important for practical application. For satisfying these requirements, NCTF (nominal characteristic trajectory following controller) has been proposed as a practical point-to-point (PTP) positioning control. However, the NCTF control system has a PI compensator which is designed without systematic procedure for obtaining the best PI compensator parameters. To overcome this problem, in this paper, fuzzy compensator is proposed and used to replace the PI compensator. The effectiveness of the proposed Fuzzy—based NCTF controller is evaluated and compared with those of normal NCTF and PID controllers through simulation. Furthermore, robustness to parameter variations of the NCTF controller with the proposed fuzzy compensator is also studied. Simulation results show that the NCTF controller with fuzzy compensator is not only effective for PTP positioning system but also robust to inertia variation.